Multiplexed fbg sensor recorded in multimode microstructured polymer optical fibre - Kalli, Kyriacos; Argyros, Alexander; Webb, David J.; Johnson, Ian P.; Large, Maryanne C J (My University, 2010)
Fibre Bragg gratings have been inscribed in multimode microstructured polymer optical fibre (POF), with a core size of 50μm. The microstructured POF (mPOF) consists of a three ring hole structure and is made purely from poly(methyl methacrylate) (PMMA). In comparison to silica fibre, POF has a much smaller Young's modulus and a much greater breaking strain; additionally multimode fibre holds advantages of ease of handling and launching conditions. A linear strain sensitivity of 1.32 ± 0.01pm/με has been measured in the range 0 to 2% strain. The fibre drawing process leads to a degree of molecular alignment along the fibre axis. This alignment can be thermally annealed out; this can induce a permanent blue shift in the Bragg wavelength of a grating fabricated prior to annealing by up to 20 nm. Utilising this, wavelength demultiplexed gratings can be fabricated using a single phase mask. As an illustration of this we present for the first time wavelength division multiplexing of the spectral response of three Bragg gratings in POF within the C-band region. Complementing this work, a technique of splicing mPOF to step index silica fibre is described using UV curing optical adhesive, allowing characterisation of Bragg gratings fabricated in this fibre.
Keywords: Wavelength division multiplexing; Fiber optics; Optical fibers; Photonic crystals; Polymers; Silica